Nepal : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1997)
This paper reviews economic developments in Nepal during 1990-97. With a new government coming to office in December 1994, progress on structural reforms stalled in 1994/95 and financial policies weakened. GDP growth slowed to 2.9 percent, reflecting adverse conditions in agriculture. The external situation deteriorated further in the first quarter of 1995/96 in part because interest rates in Nepal did not rise in line with rates in India, where monetary policy had tightened. Following a further change in government in September 1995, steps were taken to address the emerging macroeconomic imbalances.